Dendrobium moniliforme var. hongbinii (Orchidaceae: Epidendroideae), a new variety from Sichuan, China - Zheng, Bao-Qiang; Yang, Hong-Bin; Wang, Qun; Chen, Xing-Liang (Phytotaxa, 2024)
A new variety of Orchidaceae, Dendrobium moniliforme var. hongbinii, collected from Sichuan Province, China, is described and illustrated based on morphological characteristics and molecular biological analysis. It belongs to Dendrobium and is similar to D. moniliforme, from which it differs by the length of mentum is more than half of the bud, the angle is obtuse, calyx sac ends acuminate, the petals and mid-lobe are subelliptic, the ratio of mid-lobe to the labellum is 1/3. Molecular biological analysis based on nuclear markers (ITS) and plastid markers (trnL intron) indicates that D. moniliforme var. hongbinii is a variety of D. moniliforme.